Writing for visual media - Friedmann, Anthony (Focal Press, 2010)
"Writing for Visual Media looks at the fundamental problems a writer faces in learning to create content for media that is to be seen rather than read. It takes you from basic concepts to practice through a seven-step method that helps you identify a communications problem, think it through, and find a resolution before beginning to write. Through successive exercises, Writing for Visual Media helps you acquire the basic skills and confidence you need to write effective films, corporate and training videos, documentaries, web sites, PSAs, TV shows, nonlinear media, and other types of visual narratives. You'll explore your visual imagination and try out your powers of invention. The companion web site enriches the content of the printed book with video, audio, and sample scripts. It includes scripts and the video produced from them; visual demonstrations of concepts; and an interactive, illustrated glossary of terms and concepts."--Resource description page.